Active targeting of rhenium (iv) oxide (ReO2), rhenium trioxide (ReO3) and rhenium (vii) oxide (Re2O7) nanoparticles as cancer therapeutics swell-up to kill cancer cells under synchrotron and synchrocyclotron radiations - Heidari, Alireza; Hotz, Margaret; MacDonald, Nancy; Peterson, Victoria; Caissutti, Angela; Besana, Elizabeth; Esposito, Jennifer; Schmitt, Katrina; Chan, Ling-Yu; Sherwood, Francesca; Henderson, Maria; Kimmel, Jimmy (International Journal of Advanced Chemistry, 2021)
In the current research, active targeting of Rhenium (IV) Oxide (ReO2), Rhenium Trioxide (ReO3) and Rhenium (VII) Oxide (Re2O7) nanoparticles as cancer therapeutics swellâ€“up to kill cancer cells under synchrotron and synchrocyclotron radiations is investigated. The calculation of thickness and optical constants of Rhenium (IV) Oxide (ReO2), Rhenium Trioxide (ReO3) and Rhenium (VII) Oxide (Re2O7) active targeting of Rhenium (IV) Oxide (ReO2), Rhenium Trioxide (ReO3) and Rhenium (VII) Oxide (Re2O7) nanoparticles as cancer therapeutics swellâ€“up to kill cancer cells under synchrotron and synchrocyclotron radiations produced using solâ€“gel method over glassy medium through a single reflection spectrum is presented. To obtain an appropriate fit for reflection spectrum, the classic Drudeâ€“Lorentz model for parametric diâ€“electric function is used. The best fitting parameters are determined to simulate the reflection spectrum using Lovenbergâ€“Marquardt optimization method. The simulated reflectivity from the derived optical constants and thickness are in good agreement with experimental results.Â Â Â Active targeting of Rhenium (IV) Oxide (ReO2), Rhenium Trioxide (ReO3) and Rhenium (VII) Oxide (Re2O7) nanoparticles as cancer therapeutics swellâ€“up to kill cancer cells under synchrotron and synchrocyclotron radiations.Â Â